Pengaruh Persepsi Nilai, Promosi Online Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Produk Fashion Pada Aplikasi Shopee (Studi Kasus Pada Mahasiswa Universitas Panca Marga Angkatan Tahun 2020) - Rodiyatul Munawaroh; Judi Suharsono; R Hery Koeshardjono (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The purpose of this research is to describe and quantify the impact that Online Promotion, Consumer Satisfaction, and Perceived Value have on Fashion Product Purchase Decisions made using the Shopee App. Quantitative research with an interdisciplinary focus is employed. Students enrolled in the Faculty of Economics at the University of Panca Marga for the 2020 school year make up the study's population; researchers selected a sample of 40 customers using a purposive sampling approach. The data needed is in the form of a primary form of a questionnaire. Statistical Packages for the Social Sciences (SPSS) was used for the analysis. Analytical procedures such as the validity test, the reliability test, the F test, the partial test, and the dominance test. Based on the results of the partial test (t test) that has been carried out with a significance level of 5% it can be concluded that 1) Perceived Value with a tcount of 2.917 > ttable of 2.028. 2). Online promotions with a value of 3.129 > ttable 2.028. 3). Consumer satisfaction with a value of 2.754 > 2.028.